Digital Transformation in Supply Chain for Business Operational Efficiency: Transparansi dan Efisiensi Pengembangan Startupreneur pada Keuangan Digital Berbasis Teknologi Blockchain - Faturahman, Adam; Wibowo, Nugroho Prihantoni; Oganda, Fitra Putri; Zanubiya, Jihan; Green, Thomas (ADI Bisnis Digital Interdisiplin Jurnal, 2025)
The integration of digital technology with marketing strategies plays a crucial role in improving supply chain efficiency while strengthening customer satis- faction in an increasingly competitive business environment. This study aims to evaluate the contribution of digital tools such as automation, the Internet of Things (IoT), and data analytics in optimizing supply chain processes and iden- tify how such integration impacts customer perceptions and loyalty. Using a quantitative approach involving a survey of industry players, the study reveals that the adoption of digital technology not only accelerates distribution flows and improves demand accuracy but also strengthens responsiveness to consumer needs. The findings indicate that operational efficiencies achieved through digi- talization can be directly linked to increased customer satisfaction through faster, more transparent, and personalized service experiences. However, challenges such as high initial investment costs and internal resistance remain key barriers. Therefore, successful digital transformation in the context of supply chains and marketing requires a careful integration strategy focused on the long term. This study provides practical recommendations for companies in developing adap- tive, efficient, and customer-centric supply chain systems.